Penerapan Metode Pembelajaran Talking Stick dalam Upaya Peningkatan Hasil Belajar Pokok Bahasan Iklan, Sarana Komunikasi Pada Kelas VIII SMPN 1 Singosari. - Nurcahyo, Arif (Jurnal PTK dan Pendidikan, 2018)
Scope of the Indonesian Language Subject to the basic education level (VII-IX) is as follows. The text-forming language units: language sounds, phonemes, morphemes, words, word classes, phrases, clauses. The language marker in the text. Paralinguistik (pronunciation, abbreviation, intonation, tempo, gesture, and mimic). The text structure of the story genre (text eksemplum), factual genre (text recording experiment) and response genres (challenge text, critical responses). The cultural context, norms, and social context behind the birth of the text type.The results of this study indicate that the learning outcomes in the second test meeting cycle I showed an increase. The first increase is the grade value of the previous grade is 67.63. At the second meeting the first cycle increased to 76.94. Furthermore, in the range of values 76 - 100 has a percentage of 31.25% increased to 62.5%. that the learning outcomes in the first meeting test in the second cycle showed a significant increase. In the second cycle as a whole mastery of students on the material review patterns, structure and linguistic rules of advertising reached 84.38%.